INHIBITION: STUDENT’S PROBLEM IN SPEAKING CLASS - Made Yudyantara Risadi; Ni Wayan Sumariadhi; I Wayan Wijayasa (International Journal of Linguistics and Discourse Analytics, 2020)
This study aimed at figuring out the problems encountered by students in speaking class and the solutions for the problems found. Based on the library research, compiling many theories and it was found that students encounter many problems in speaking class, one of them is inhibition. Inhibition is a state where the students feel afraid of making mistake when performing a speaking task. This problem can be solved by giving the students positive feedback after performing, motivating students to speak before performing, creating a harmonious atmosphere that can reduce students’ nervousness and giving communication training to improve students’ self-confidence